Reservoir architecture and remaining oil distribution of deltaic front underwater distributary channel - Congjun FENG; Zhidong BAO; Ling YANG; Xiong SI; Guibin XU; Xiong HAN (Petroleum Exploration and Development, 2014)
Taking the J19 dense well network area in the Fuyu Oilfield as a case, combined with field outcrop and modern shallow water delta sedimentary model and using coring and logging data, this paper puts forward a comprehensive analysis method for reservoir architecture of deltaic front underwater distributary channel single sand body. The causes and sedimentary evolution mechanisms for foresets of retained type, destructive type and the mixed type and for foreset sandbodies of prograding type, retrograding type and aggrading type are summarized. The calibration of rock and logging, fitting formula, dense spacing wells and pair wells data are used to ascertain the foresets and foreset sandbodies. The models of three-dimensional reservoir architecture are set up. The analysis of remaining oil shows that foreset controls the vertical distribution of the remaining oil, while in the internal of foreset sandbodies, the remaining oil is enriched in the updip direction. Key words: deltaic front, underwater distributary channel, single sand body, reservoir architecture, remaining oil